(untitled) (The Research of Medical Science Review, 2025)
Background: Second-trimester abortions (12-28 weeks gestation) constitute 10-15% of terminations globally and carry higher risks of maternal morbidity and mortality compared to first-trimester procedures, particularly in low-resource settings. Misoprostol, a prostaglandin E1 analog, is commonly used for medical abortion via oral or vaginal routes in Pakistan. Evidence suggests sublingual administration might be more effective, but local data comparing sublingual and oral routes is lacking. This study aims to fill this gap.Objective: To compare the effectiveness of oral versus sublingual misoprostol in achieving complete abortion within 24 hours in patients undergoing second-trimester medical abortion (14-24 weeks gestation).Method: This randomized controlled trial was conducted at the Department of Gynae and Obs, Jinnah Hospital, Lahore, over 6 months. 92 consenting women aged 18-35 years, presenting between 14-24 weeks gestation with fetal demise requiring abortion, were included using non-probability consecutive sampling. Patients were randomly assigned via lottery method to two groups (n=46 each). Group O received 400µg misoprostol orally every 4 hours, and Group S received 400µg misoprostol sublingually every 4 hours, for a maximum of 4 cycles. Effectiveness was defined as complete expulsion of products of conception within 24 hours, confirmed by ultrasound. Data were analyzed using SPSS v25, with the Chi-square test used to compare effectiveness between groups (p<0.05 considered significant).Result: Complete abortion within 24 hours was achieved in 35 out of 46 patients (76.1%) in the sublingual group (Group S) compared to 22 out of 46 patients (47.8%) in the oral group (Group O). The difference in effectiveness between the sublingual and oral routes was statistically significant (p = 0.004).Conclusion: Sublingual administration of misoprostol is significantly more effective than oral administration in achieving complete medical abortion within 24 hours for patients in the second trimester. Utilizing the sublingual route may lead to improved outcomes, potentially reducing complications and the need for surgical intervention in this patient population.